Bark stripping of young Pinus sylvestris by Alces alces on the individual, stand, and landscape level in Sweden - Faber, William E.; Thorson, Erik M. (Canadian Journal of Forest Research, 1996)
Physical characteristics of Scots pine (Pinussylvestris L.) trees bark stripped by moose (Alcesalces L.) and frequencies of bark stripping were quantified at the Grimsö Wildlife Research Area in south-central Sweden during July 1995. Twenty-one young Scots pine stands evenly distributed over two areas of differing forest productivity were included in the study. Each stand was systematically plot-surveyed to determine the frequency of affected Scots pine trees. Additionally, we quantified data (i.e., 13 variables) on 420 recently (i.e., spring 1995) bark-stripped pine trees located through visual walking surveys of each stand. Less than 3% of the trees within the susceptible height range (1.5–4.0 m) were bark stripped annually, and 99% of these trees were between 1.5 and 4 m in height and wounds were concentrated within the 3- and 4-year-old internodes. There was a weak positive relationship between frequency of bark stripping and forest productivity at the stand and landscape levels, whereas weak negative relationships were found between bark-stripping frequency and stand size and bark-stripping frequency and pine stem density. Overall, the results suggest bark stripping has a minor impact on the trees. Forestry practices to reduce bark-stripping damage are discussed.